WAKAF DALAM PERSPEKTIF HUKUM ISLAM - Taufiq . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Waqf is a legal act in the field of law material that has long known by the public Isalam Indonesia, as a form of social and religious. Although endowments as a highly recommended act in Islam, its implementation should  be  based  on harmonious terms of endowments.  Besides relating  to waqf land ownership should heed government regulation number 28 of 1997 and Law no. 41 year 2004 about endowments.Legality  of waqf in  Islam contained  in the  Qur'an and Al-Hadith  and the  results of  ijtihad,  as contained  in the  Qur'an Surah  Al-Hajj:  77, Ali Imron:  92. In  the  Qur'an-mail  Ali Imron:  92, property diwakafkan more mainstream is a well-loved treasures, the treasure which has a value of more benefit when compared with other treasures owned by Wakif. At first waqf in Islam is when Umar getting a piece of land in Khaibar. Umar asked the Prophet Muhammad,: Are orders to me in connection with this land that you can, "replied Muhammad peace be upon him, if you like, hold the  land  and you sedekahkan benefits. (HR,  Buchori Muslim). Although endowments are  highly  recommended  in Islam,  but  it should  not  be done indefinitely, endowments should  not be  done all  the  property belonging  to diwakafkan,  because  it would  be detrimental to the heirs, according to the Islamic waqf justified only a third of the properties. Keywords: Endowments in the Perspective of Islamic Law